Thor's Return of the Giant Geirrod's Red-Hot Missile Seen in a Cosmic Context - Lyle, Emily B. (Temenos, 2019)
Discussion of the specific episode is preceded by a brief presentation of current theory concerning Indo-European myth in its cosmological framework to provide context. In the cosmological view sketched by Michael Witzel in The Origins of the World's Mythologies, the hero/young god must engage in a series of feats to create the conditions for human life to flourish. I have suggested that the conditions before the hero's actions in the Indo-European context are envisaged as the extremes: too close; too hot; too dry; and too wet. It is argued that this particular threat is too hot' and comes from a giant figure who is one of the old gods, probably identifiable as Odin. When Geirrod throws a red-hot missile at Thor, Thor catches it and kills the giant when he sends it back. The related stories of Thor's visit to Utgarthaloki and Thorstein's visit to Geirrod are also treated, and attention is drawn to Welsh and Irish parallels which make an equivalence between thrown weapon and destructive gaze. It is suggested that the story may culminate in the motif of eye as star found separately.